Serbian Islamophobia: St. Sava, Njegoš & Srđa Trifković - Omer, Spahic (Dar al-Wahi Publication, 2023)
In my book titled “Islamophobia and Islamic Moderation”, which was published in 2022 by the Dar Al Wahi Publication in Kuala Lumpur, some general aspects of Islamophobia: definition, characteristics, history and manifestations, have been dealt with. This book has a very specific aim, namely to examine the concept and phenomenon of the Serbian Islamophobia. This is done by analysing the Islamophobic roles and contributions of three prominent Serbian personalities, exemplifying thus three different eras and three mutually complementing approaches. Those personalities are: Saint Sava (d. 1236), who lived prior to the arrival of the Osmanlis (Ottomans) on the Balkan Peninsula; Petar II Petrović Njegoš (d. 1851), whose epoch was marked by the waning of the Osmanli power in the region and beyond; and Srđa Trifković (born in 1954), whose case represents the turbulent modern times. The adjective “Serbian”, as in the title of the book, is synonymous with the adjective “Serb”, encompassing Serbia as a country and the Serbs as a people. The book shows that in addition to the typical Western epicentres of Islamophobia - such as France, America and England - Serbia and Serbdom (the Serb people wherever they lived), though often discounted in Islamophobic discourses, played a prominent role, too. They excelled both in theory and practice. The Serbian lands, culture and thought developed into hotbeds of Islamophobia in compliance with the highest international standards. Right through the ages, the European Islamophobic counterparts had constantly something to learn from the Serbs and their Islamophobia paradigm. The avant-garde Islamophobes of Serbia stood at the forefront of guarding Europe and defending its increasingly endangered Christian character and values. This way, Serbia served as a bulwark of the self-proclaimed Christian Europe against the peril of Islam (the antemurale myth). It follows that the 1992-1995 aggression against Bosnia, punctuated by bloodbaths, genocide and loads of other unspeakable crimes against humanity, was envisaged centuries ago, was planned in the Serbian corridors of power – irrespective of where exactly: in Serbia, Bosnia or somewhere else – and was implemented in the arena of Bosnian cities and villages many of which were turned into workshops of inexpressible horrors. The book is divided into five chapters: Chapter One: Saint Sava of Serbia and Islamophobia; Chapter Two: The Maturation of the Serbian Islamophobia: the Role of “The Mountain Wreath” (“Gorski Vijenac”); Chapter Three: Elements of Islamophobia in Njegoš’s “The Mountain Wreath”; Chapter Four: The Serbian Islamophobia Goes Global: the Role of Srđa Trifković; Chapter Five: Responding to Srđa Trifković’s Drivels.